A Comparison of Benefit Cost and Cost Utility Analysis in Practice: Divergent Policies in Sweden - Lars Hultkrantz; Mikael Svensson (Örebro University School of Business, 2012)
We compare state-of-the-art implementation of Benefit Cost Analysis (BCA) and Cost Utility Analysis (CUA) as tools for making priorities in allocation of national public funds in the transport sector and health sector, respectively, in Sweden. While the principal distinctions between these methods are well known, less notice has been given to a number of other differences that have emerged as national and international practices have evolved over time along separate lines. We compare cost and benefit components and economic parameter values and find some surprising disparities. There are inconsistencies, both across methods and within each method. Both can be improved by learning from the other. We also find that some current practices conflict with the underlying welfare theory and/or insights from recent empirical analysis.
Keywords: D61; H51; I18; 330; Benefit Cost Analysis; Cost Utility Analysis